The Effect of Organic Cow Manure Pellets (Bos taurus Linn.) with Additional Moringa Leaf (Moringa oleifera Lam.) on The Growth of Dumbo Catfish Seedlings (Clarias gariepinus Burch.) - Prihartini, Ni Luh Wayan Widhi; Razak, Abdul (Jurnal Biologi Tropis, 2024)
One of the factors that influences the growth of African catfish is feed. Cow dung and Moringa leaves are one of the ingredients for making organic pellets that can support the growth of catfish. This is because Cow Manure and Moringa Leaves contain quite high levels of protein. This research aims to determine the effect of organic cow dung pellets with the addition of Moringa leaves on the growth of African catfish seedlings. This type of research is an experiment by making organic pellets from cow dung and Moringa leaves with different treatments. The data obtained were analyzed statistically using the ANOVA test via the SPSS 21 application. The results showed that treatments A, B, and K+ were not effective because the growth of African catfish was slow. Treatment C obtained good results with an average fish length of 3,173-4,181 cm and weight of 6-9 grams. Furthermore, the DNMRT test results were 3.926d and 7.6b. Almost approaching the growth of Dumbo K-Catfish. Increase in length of Dumbo K Catfish - 4,705-5,142 cm and weight 8-12 gr. Furthermore, the DNMRT test results were 4.8166e and 10.2c. The composition of 25% Cow Manure and 75% Moringa Leaves in organic pellets can be used as an alternative feed ingredient for Dumbo Catfish. In conclusion, the effectiveness of organic pellets made from Cow Manure and Moringa Leaves is close to chemical pellets.